Effect of osseous defect on periodontal ligament stress under normal masticatory force: A three-dimensional finite element analysis of mandibular second molar - Bhavya Shetty; Safiya Fatima Khan; Khadijathul Irfana; Manjusha Nambiar (Journal of Indian Society of Periodontology)
Background: Finite element model (FEM) offers an ideal method for the accurate modeling of tooth periodontium with its complicated three-dimensional (3D) geometry. The present study aimed to assess periodontal ligament (PDL) stress under normal masticatory force in the mandibular second molar with and without osseous defect at two different angulations. Materials and Methods: Cone-beam computed tomography was used to collect 3D information on the mandibular second molar. Four 3D models were designed using FEM. The first was a mandibular second molar with normal bone support. The second, third, and fourth models had three-wall defects where the mesial wall had bone loss up to 1/3rd, 2/3rd, and complete root length, respectively. Vertical and Oblique forces were applied to each model and statistical analysis was carried out using Von Mises stress analysis. Results: Von Mises stress on PDL was seen in the cervical area when the bone was lost up to one-third of root length. As bone loss increases, the stress is concentrated in the apical region and it increases with an increase in bone defect. Maximum PDL stress was 1.84 × 10−05 megapascal (MPa) under vertical force and 1.0 × 10−04 under oblique force. Maximum stress on cortical bone was 14.019 MPa under vertical force and 45.939 MPa under oblique force and the values were statistically significant. Conclusion: Stress on PDL and cortical bone was four times higher under oblique force compared to vertical force. As periodontal support reduces, stress increases and gets concentrated on the apex, leading to apical extension of resorption. Teeth with compromised periodontium are more predisposed to occlusal trauma.